KOMPETENSI DAN KUALITAS LAYANAN KARYAWAN TERHADAP KESELAMATAN PENERBANGAN - Wynd Rizaldy; Agus Setiawan (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2015)
The objective of the research is to determine the correlation between Employees’ Competence (Ko) and Service Quality (Ku) with Aviation Safety (Ks). The research was conducted at PT. Jasa Angkasa Semesta Tbk Jakarta Eksport warehouse with n = 45 respondent decided fixed due to saturate sample. Data analysis uses simple linear regression, multiple linear regression, simple correlation and partial correlation. The result are as follow ; (1) there is positive correlation between employees’ competence (Ko) and aviation safety (Ks), (2) there is positive correlation between service quality (Ku) and aviation safety (Ks) (3) there is positive correlation between employees’ competence and service quality all together toward aviation safety . Based on the result of research, aviation safety could be enhanced by increasing employees’ competence and service quality.